Treatment with nintedanib is as effective and safe in patients with other connective tissue diseases (CTDs)-interstitial lung disease (ILD) as in patients with systemic sclerosis-ILD: A multicenter retrospective study - Misirci, Salim; Ekin, Ali; Yagiz, Burcu; Coskun, Belkis Nihan; Basibuyuk, Fatma; Birlik, Ahmet Merih; Pehlivan, Yavuz (Springer London Ltd, 2025)
Objective The aim of this study is to assess the efficacy and safety of nintedanib (NTD) therapy in a real world population of patients with connective tissue diseases related interstitial lung disease (CTDs-ILD). Methods Our multicenter retrospective study included patients with a CTD-ILD diagnosis who started NTD treatment due to the development of PPF during follow-up. The results of the percentage predicted forced vital capacity (%pFVC) and percentage predicted diffusion capacity (%pDLCO) of patients before NTD treatment and 6, 12 and 18 months after the start of NTD treatment were evaluated. In addition, the patients were divided into two groups, SSc-ILD and other CTDs-ILD, and compared in terms of the efficacy and safety of the NTD. Results In all patients (n = 66), %pFVC and %pDLCO values stabilised after 6, 12 and 18 months compared to baseline values. All patients received at least one immunosuppressive therapy in combination with NTD treatment. The most common side effect after NTD treatment was diarrhoea (n = 20, 30.3%). When we divided the patients into two groups, SSc-ILD (n = 35) and other CTDs-ILDs (n = 31), no significant difference was found between the groups in the change in %pFVC (p values = 0.498, 0.595 and 0.376, respectively) and in the change in %pDLCO (p values = 0.817, 0.185 and 0.399, respectively) at 6, 12 and 18 months follow-up. Again, there was no statistically significant difference between the two groups in terms of adverse events and safety data after NTD treatment (p > 0.05). Conclusion In summary, the use of NTD in combination with immunosuppressive therapies was effective and safe in SSc-ILD patients as well as in other CTDs-ILD patients.
Keywords: Connective tissue disease; Interstitial lung disease; Nintedanib; Real-world data; Systemic sclerosis